Scaling concept II rowing ergometer performance for differences in body mass to better reflect rowing in water - Nevill, A. M.; Beech, C.; Holder, R. L.; Wyon, M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
We investigated whether the concept II indoor rowing ergometer accurately reflects rowing on water. Forty-nine junior elite male rowers from a Great Britain training camp completed a 2000 m concept II model C indoor rowing ergometer test and a water-based 2000 m single-scull rowing test. Rowing speed in water (3.66 m/s) was significantly slower than laboratory-based rowing performance (4.96 m/s). The relationship between the two rowing performances was found to be R2=28.9% (r=0.538). We identified that body mass (m) made a positive contribution to concept II rowing ergometer performance (r=0.68, P<0.001) but only a small, non-significant contribution to single-scull water rowing performance (r=0.039, P=0.79). The contribution that m made to single-scull rowing in addition to ergometer rowing speed (using allometric modeling) was found to be negative (P<0.001), confirming that m has a significant drag effect on water rowing speed. The optimal allometric model to predict single-scull rowing speed was the ratio (ergometer speed ×m-0.23)1.87 that increased R2 from 28.2% to 59.2%. Simply by dividing the concept II rowing ergometer speed by body mass (m0.23), the resulting "power-to-weight" ratio (ergometer speed×m-0.23) improves the ability of the concept II rowing performance to reflect rowing on water.